Bio-reduced Ag nanoparticle decorated on ZnO for enhancement of photocatalytic reduction of hexavalent chromium and photocatalytic degradation of rhodamine B - Chuaicham C. (2023)
Ag nanoparticles reduced by organic components extracted from Jasmine tea leaves were decorated by a hydrothermal reaction on ZnO to fabricate AgNPs@ZnO composite, and then the composite was applied for photocatalytic reactions to degrade rhodamine B (RhB) and reduce hexavalent chromium (Cr(VI)). The produced composite (AgNPs@ZnO) was optically and physicochemically characterized to better understand the impact of the development of the AgNPs-ZnO heterojunction when compared to that of pure ZnO. The optimized AgNPs@ZnO reduced more than 95% of 10 mg/L Cr(VI) in 60 min and degraded more than 95% of 10 mg/L RhB in 180 min, with a rate constant around five times for Cr reduction and three times for RhB degradation faster than that of pure ZnO, due to its superior capacity to separate and transport photogenerated electron-hole pairs, as evidenced by a drop in photoluminescence intensity. Furthermore, when AgNPs were placed on the surface of ZnO in the composites, surface defects were generated on ZnO, as confirmed by the energy-resolved distribution of electron trap (ERDT) pattern for AgNPs@ZnO, indicating the formation of new electron trapping levels. This might cause a reduction of the energy band gap, resulting in the enhancement of light adsorption and reduction of charge recombination. Therefore, the present bio-induced composite of AgNPs@ZnO opens up new possibilities for photochemical purification technology in aquatic environments.